2014
DOI: 10.1186/1475-9276-13-35
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic inequalities and body mass index in Västerbotten County, Sweden: a longitudinal study of life course influences over two decades

Abstract: IntroductionLife course socioeconomic inequalities in heart disease, stroke and all-cause mortality are well studied in Sweden. However, few studies have sought to explain the mechanism for such associations mainly due to lack of longitudinal data with multiple measures of socioeconomic status (SES) across the life course. Given the population health concern about how socioeconomic inequality is related to poorer health, we aim to tackle obesity as one of the prime suspects that could explain the association b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
38
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(42 citation statements)
references
References 43 publications
3
38
1
Order By: Relevance
“…Power and Elliott, 2006; Kuh et al, 2011) and several Scandinavian countries (e.g. Padyab and Norberg, 2014) the populations studied were largely homogeneous with respect to race. Here we describe a study that prospectively assesses social conditions, cognitive abilities, and emerging health as life course processes that may be involved in the generation of health inequalities by race and SES in the adult life.…”
mentioning
confidence: 98%
“…Power and Elliott, 2006; Kuh et al, 2011) and several Scandinavian countries (e.g. Padyab and Norberg, 2014) the populations studied were largely homogeneous with respect to race. Here we describe a study that prospectively assesses social conditions, cognitive abilities, and emerging health as life course processes that may be involved in the generation of health inequalities by race and SES in the adult life.…”
mentioning
confidence: 98%
“…A positive relationship between the compliance of diets to official nutritional recommendations (henceforth: diet quality) and diet cost among the general population is well established through previous studies: A higher diet cost is associated with lower energy density and/or higher intake of key nutrients ( 1 3 ), higher consumption of fruit and vegetables ( 1 , 4 6 ), higher consumption of fish ( 1 , 5 ), and higher nutritional density ( 1 , 2 , 5 , 7 ). Furthermore, studies have shown better diet quality among high socioeconomic status (SES) households ( 8 , 9 ) and a higher risk for diet-related illnesses among low SES individuals in Sweden ( 10 12 ) and elsewhere ( 13 16 ). Foods that are more nutrient rich, more energy poor, and generally classified as ‘healthy’ are often more expensive than alternatives ( 17 21 ).…”
mentioning
confidence: 99%
“…With respect to middle‐aged women, a life course characterised by lack of resources and adversity also leads to increased risk of obesity (Gustafsson et al . , Padyab and Norberg ) and higher biological risks of metabolic syndrome, a condition highly related to the development of chronic diseases (Gustafsson and Hammarstrom ). While life course approaches in qualitative sociology have used socioeconomic variables to explain poor health outcomes (Stansfeld et al .…”
Section: Resultsmentioning
confidence: 99%
“…Various causes such as adverse life circumstances, repeated personal experiences of failure, and long‐term exposure to low economic, cultural or social capital, have been identified to negatively influence weight and health, and to increase the risks of chronic diseases in middle‐aged women (Gustafsson et al . , Gustafsson and Hammarstrom , Padyab and Norberg ). Despite research on the preventive function of health practices (exercise, healthy eating and weight management), few studies have specifically focused on the health and lifestyle concerns of underprivileged women after the menopausal transition.…”
Section: Socio‐economic Status Weight and Menopausementioning
confidence: 97%